PENGARUH TURNOVER KARYAWAN TERHADAP KUALITAS PELAYANAN WEDDING ORGANIZER - Afelino, Lazio Vaulia; Mananda, I GPB Sasrawan; Wijaya, Ni Made Sofia (Jurnal Analisis Pariwisata; Vol 20 No 01 (2020): Jurnal Analisis Pariwisata (2020), 2021)
The development of tourism in Bali makes wedding organisers a c ontinuously increasing business, one of which is PT Bali VIP Indonesia that handles more than 50 weddings annually. However, during the preparation process, tourists as their main customers were faced with numerous coordination challenges due to the high turnover rate within the company. The objective of this research is to identify the impact of employee turnover on the quality of service of PT Bali VIP Indonesia. This research was conducted at PT Bali VIP Indonesia, taking into calculation 30 former employees and 30 tourists as samples determined using the saturated samples method. Data on this research were gathered by the distribution of questionnaires towards former employees and former tourist customers of PT Bali VIP Indonesia. Subsequently, the data were assessed using descriptive analysis, validity and reliability testing, normality test, and simple linear regression analysis. The result of this study shows that there is a negative impact between turnover and the quality of PT Bali VIP Indonesia wedding organiser services with the value of Sig. 0,18 < 0,05. However, the turnover variable has a low correlation (R = 0.427) with the quality of service variable of PT. Bali VIP Indonesia wedding organiser and the effect of employee turnover on service quality is 18.3%. Therefore, in conclusion, the negative result explains that the declining quality of service will decrease the quality of service given by the employee to the tourist as customers.